Surfactant Protein (SP) induces preterm birth by promoting oxidative stress via upregulating Storkhead-Box Protein 1 (Clinics, 2022)
Preterm birth is the leading cause of infant mortality. The mechanisms that instigate preterm birth remain elusive and this makes it difficult to predict or prevent preterm birth. In this study, the authors found that SP-A induced pathological damage to the placenta and promoted preterm birth. Through mechanism, SP-A promoted the expression of STOX1 which further promoted the oxidative stress in the placenta by inhibiting the activities of a series of antioxidant enzymes including SOD, CAT and GSH-Px. SP-A also induced dysregulation of arginine metabolism by inhibiting NOS2 and ARG2. Overexpression of STOX1 aggravated SP-A induced oxidative stress, pathological damage, and preterm birth, whereas knockdown of STOX1 alleviated SP-A induced oxidative stress, pathological damage and preterm birth. The present study uncovers that SP-A induces preterm birth by promoting oxidative stress via upregulating STOX1, which provides new targets for the prediction and prevention of preterm birth.